Nonsurgical Delay of Dorsal Rat Cutaneous Flap Using Botulinum Toxin Type A - Yildirim, Alpagan M.; Okur, Ihsan; Orter, Zubeyir; Uysal, Ata (Lippincott Williams & Wilkins, 2008)
[Abstract Not Available]